Fortalecimiento de la competencia comunicativa escritora en los estudiantes de básica primaria de la Institución Educativa Departamental Pio X del municipio de Chipaque, Cundinamarca (2017)
This research project is a proposal aimed at strengthening narrative production in elementary school students through the implementation of workshops. Based on the theory of Teun Van Dijk (1980) and other research that not only contributed to design the strategies but also as a reference in the elaboration of the categories. To answer the research question, an action research was carried out with a group of 24 students. The effectiveness of the workshops was evaluated through the progress of the students, analyzed from the categories. The result was positive because of the progress students made in the performance of their writing.